Doped-Ceria Electrolytes Synthesis, Sintering and Characterization - Spiridigliozzi, Luca (SpringerBriefs in Applied Sciences and Technology,, 2018)
This book provides an overview of fuel cell technology and, in particular, of Solid Oxide Electrolysis Cells (SOFCs). Each chapter highlights the effects of different synthesis parameters and/or adopted sintering method, clarifying both advantages and disadvantages pointed out by different experimental campaigns. The book focuses on Doped-Ceria Electrolytes, presenting an engineered production process of GDC/SDC electrolytes by using a combination of wet chemical synthesis and/or alternative sintering techniques, capable of enhancing electrolytes microstructural features and electrical properties at reduced temperature and time. The author proposes useful guidelines to produce dense and high-preforming ceria-based electrolytes for IT-SOFCs.